ANALYSIS OF THE EFFECTIVENESS OF PUBLIC DEBT MANAGEMENT POLICY (World of finance, 2020)
Introduction. The effectiveness of debt policy is determined by the structure of the debt in terms of maturities, currencies, interest rates and the real ability of the government to fulfill its obligations in a timely and without threat to the financial system.The purpose is to analyze the effectiveness of Ukraine’s public debt management in recent years and to evaluate the impact of factors on its effectiveness.Methods. The following methods were used to achieve the goal: system-structural analysis, theoretical generalization, induction and deduction, economic-statistical and settlement-analytical methods, abstract-logical method.Results. It is argued that to assess the effectiveness of public debt management, in addition to the benchmarks, it should also take into account the level of interest rates on government bonds, change in the exchange rate UAH / USD, GDP growth rate. In this regard, the mathematical model is used to analyze the effectiveness of public debt management by comparing the ratio of debt service cost to GDP growth and the ratio of government debt to GDP ratio.Perspectives. The analysis makes it possible to confirm that the debt management policy in 2018-2019 was the least effective as the gap between the value of the public debt growth rate in GDP and the debt service cost ratio is approaching zero. According to the results of the study, a number of problems that arise in the process of public debt management are identified and new indicators are proposed to evaluate its effectiveness.